Penerapan Model Pembelajara cooperative Tipe Think Talk Write (TTW) dalam Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika Pada Siswa Kelas V SD Negeri 4 Seraya Barat - I Komang Sulitra Astawan (Jayapangus Press, 2021)
This research was conducted at SD Negeri 4 Seraya Barat. This type of research is classroom action which is carried out in two cycles. The subjects of this study were the V grade students of SD Negeri 4 Seraya Barat in the odd semester of the 2019/2020 school year, totaling 14 people. Each cycle consists of four stages of activities, namely planning, implementing actions, observing, evaluating, and reflecting. The data collected in this study are: (1) student activities, and (2) student learning outcomes. Based on the results of data analysis and discussion of this research, the following conclusions can be drawn. 1) The application of the Think Talk Write (TTW) cooperative learning model in mathematics learning can improve the learning activities of fifth grade students at SD Negeri 4 Seraya Barat in the odd semester of the 2019/2020 school year. Student learning activity in Cycle I was 10.64 while student learning activity in Cycle II was 14.43. Thus there was an increase of 3.79 from cycle I to cycle II. 2) The application of the Think Talk Write (TTW) cooperative learning model in mathematics learning can improve the learning outcomes of fifth graders at SD Negeri 4 Seraya Barat in the odd semester of the 2019/2020 school year. Student learning outcomes in cycle I were 73.93 while student learning outcomes in cycle II were 90.36, thus an increase of 16.43 from cycle I to cycle II.